COMMUNITY GROUP CARING FOR HEALTHY LUNGS (MADUPASEH) TOWARDS THE PREVENTION OF PULMONARY TUBERCULOSIS IN YOKA VILLAGE - Rohmani Rohmani; Frengky Apay; Ardhanari Hendra Kusuma; Ester Rumaseb (Caring : Jurnal Pengabdian Masyarakat, 2022)
Tuberculosis (TB) is an infectious disease caused by infection with the bacterium Mycobacterium tuberculosis. The source of transmission is tuberculosis patients with positive Acid Resistant Bacillus (positive BTA) through splashes of sputum droplets that they emit. Indonesia is the country with the second highest number of new cases in the world after India. The purpose of this community service is to empower the people of Yoka Village in the Prevention of Pulmonary TB by forming a Healthy Lung Care Community (MADUPASEH). The method in this implementation is to conduct a Focus Group Discussion (FGD) with the Yoka Village Government and the Head of the Yoka Health Center to discuss the problems in Yoka Village. The result: this community service was attended by the Head of Yoka Village along with village government staff, the community, ondoafi leaders, ondofolo, youth leaders, women leaders, and TB Paru cadres in Yoka Village.